Promoting Effective Consultation? Assessing the Impact of the ICE Regulations. (28th June 2011) - Hall, Mark; Hutchinson, Sue; Purcell, John; Terry, Michael; Parker, Jane
Abstract Drawing on evidence from longitudinal case studies in 25 organizations, this article examines whether information and consultation (I&C) bodies established in the context of the UK's Information and Consultation of Employees Regulations 2004 have been the vehicle for effective consultation, based on objective criteria. Assessed against the regulations' default provisions that require I&C concerning strategic business issues and major organizational change, a substantial minority of participating organizations were categorized as 'active consulters', while a majority were 'communicators'. The differing trajectories of I&C primarily reflected internal organizational dynamics, particularly management's approach to consultation. Beyond providing the catalyst for managerial moves to introduce I&C, the influence of the statutory framework proved largely peripheral.